Communication and well-being in patients and caregivers in a palliative care unit - Pascual, Antonio; Blasco, Tomás; Rufino, María; Güell, Ernest; Ramos, Adelaida (Psicooncología, 2010)
Objective: The aim of the study is to know the relationship between communication and well-being, both in patient and caregiver, when patient is assisted in Palliative Care Unit. Method: Thirty-two patients were assessed at the Palliative Care Unit in Hospital de la Santa Creu I Sant Pau at Barcelona, using a structured interview. The following features were registered: whether the patient maintained a communication with his/her caregiver; whether the patient told to the caregiver his/ her main concern, and whether the patient was satisfied with this communication. Using the same structured interview, 25 caregivers of these patients (one by patient) were also assessed. Well-being in patients was assessed by the anxiety, depression and well-being items from the ESAS scale. Well-being in caregivers was assessed by the HAD. Results: Patients who were not satisfied with communication had higher scores in depression than patients who were satisfied, although this difference did not reach statistical significance. On the other hand, depression levels were higher in patients and caregivers in those cases were patient was aware of his/ her state. Conclusions: Although the expected relationship between communication and wellbeing has not been observed, it is discussed that this could be done by some methodological limitations of the study (such as the low number of cases assessed and the use of measure tools which could not be suitable for this situation). Thus, more studies analyzing communication and well-being are needed. Furthermore, data provided by the study highlight that the relationship between communication and wellbeing must be carefully studied in patients who are aware of the evolution of their disease.
Keywords: Communication; Well-being; Anxiety; Depression; Palliative care